The role of pulses in sustainable and healthy food systems - McDermott, John; Wyatt, Amanda (Wiley, 2017)
Improving nutrition is a development priority, particularly in low- and middle-income countries (LMICs) in Africa and South Asia, in which there is a persistent burden of undernutrition and increasing obesity. Healthy food systems can play a necessary role, aligned with other multisectoral actions, in addressing this challenge. Contributing to improved nutrition and health outcomes through food-based solutions is complex. In considering the role that pulses can play in addressing this challenge, there are useful conceptual frameworks and emerging lessons. National food systems in LMICs provide limited diet quality. Foods for a healthy diet may be produced locally, but they increasingly rely on improved markets and trade. What might be done to transform food systems for healthier diets, and what role can pulses play? Food systems innovations will require a convergence of technical innovation with smarter institutional arrangements and more effective policies and regulations. In many countries in Africa and South Asia, pulses can make important contributions to healthier diets. Options for supporting pulses to make a greater contribution to healthier diets include increasing the efficiency of pulse supply chains, creating more effective public–private institutional arrangements for innovation, and establishing policies, regulations, and investments that are nutrition sensitive.